Table 1_Ovine macrophage identity and plasticity: novel insights into CSF-driven polarization and species-specific responses.docx - Yanina P. Hecker (22679417) (2025)
Macrophages (MØs) are pivotal immune cells exhibiting significant plasticity that has been widely studied in human and murine models. Granulocyte-macrophage colony-stimulating factor (GM-CSF) and macrophage colony-stimulating factor (M-CSF) are key regulators of macrophage differentiation from monocytes. In this study, we comprehensively investigated the immunophenotypic, functional, and transcriptomic profiles of ovine MØs differentiated with GM-CSF (GM-oMØs) or M-CSF (M-oMØs) to provide a more nuanced understanding of their activation states. After 7 days, GM-oMØs displayed a smaller, more varied morphology with lower cell yields compared to the larger, uniformly amoeboid M-oMØs. Immunophenotypically, M-oMØs showed significantly higher CD163 expression, consistent with human M-MØs, while CLEC5A was uninformative for differentiation. Transcriptomic analysis, complemented by qPCR and ELISA, revealed clearly distinct profiles, with GM-oMØs exhibiting a pronounced pro-inflammatory phenotype and showing significantly higher expression of 408 genes, mostly associated with interferon and inflammatory response pathways, a feature that aligns with the functional and phenotypic characteristics of human and mouse GM-MØ. Conversely, M-oMØs displayed a regulatory and anti-inflammatory profile, marked by a significantly higher expression of IL-10 and a set of 248 genes involved in cellular homeostasis. Notably, LPS stimulation dramatically shifted the M-oMØ phenotype toward a pro-inflammatory state, unequivocally demonstrating their substantial plasticity, and mirroring human M-CSF-polarized monocytes. Our findings fundamentally challenge the prevailing M1/M2 simplification in ovine macrophage biology and provide a robust foundation for selecting appropriate in vitro macrophage models for future investigations into ovine host defense and disease pathogenesis. This study demonstrated that M-oMØs exhibit greater plasticity, making them more suitable for pathogen-host interaction studies. Unlike GM macrophages, which already have a defined phenotype, M-oMØs more accurately reflect the dynamic immune response induced by a pathogen in the host.